4(x+2)=3x+11

Simple and best practice solution for 4(x+2)=3x+11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+2)=3x+11 equation:


Simplifying
4(x + 2) = 3x + 11

Reorder the terms:
4(2 + x) = 3x + 11
(2 * 4 + x * 4) = 3x + 11
(8 + 4x) = 3x + 11

Reorder the terms:
8 + 4x = 11 + 3x

Solving
8 + 4x = 11 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
8 + 4x + -3x = 11 + 3x + -3x

Combine like terms: 4x + -3x = 1x
8 + 1x = 11 + 3x + -3x

Combine like terms: 3x + -3x = 0
8 + 1x = 11 + 0
8 + 1x = 11

Add '-8' to each side of the equation.
8 + -8 + 1x = 11 + -8

Combine like terms: 8 + -8 = 0
0 + 1x = 11 + -8
1x = 11 + -8

Combine like terms: 11 + -8 = 3
1x = 3

Divide each side by '1'.
x = 3

Simplifying
x = 3

See similar equations:

| 3x^2+10+8=0 | | 3p^2-28=27p | | 4(n-1)=n+14 | | 4y^3-3=-12y^2+y | | 10+2z=20 | | -6+x=-10 | | 12t-1=14t-5 | | 8k+10=13k-5 | | 3v^2-7v-20= | | 3a=5a-18 | | 6(x+2)=3(x-5) | | 5x+37=14x-62 | | x^2+5x+18=9 | | 4x+7=x+16 | | 15r+22=97 | | 3(x-4)+5(x+3)=2(3x-5)-6 | | 6(2x-5)=42 | | -4x+2(4-3x)=8-10x | | 9x-21=3+3 | | 3r+12=r+34 | | 4p+8=10p+2 | | -x^2+50x-350=0 | | 8t^2-6t=9 | | x^5-x^4+9x^3-9x^2=0 | | 2x+3=24 | | 5x^2+36x+36=0 | | 6(x-8)-(2x-2)=5x-1 | | .5(20z+18)-8=9(z-3) | | 7x+19y=-3 | | -4c+1=-7 | | 12n-6=4n+10 | | 3(y+-4)+9(y+1)= |

Equations solver categories